Fossil penguins. Bulletin of the AMNH - Simpson, George Gaylord, 1902-; Scarritt Patagonian Expedition 1933-1934) (New York : [American Museum of Natural History], 1946)
99 p. : ill., map 27 cm. Includes bibliographical references (p. 97-99).